Noncompliance to Diet and Medication among Patients with Type 2 Diabetes Mellitus in Selected Hospitals of Kathmandu, Nepal - Kafle, Nisha Kusum; Poudel, Resham Raj; Shrestha, Sushan Man (Journal of Social Health and Diabetes, 2018)
Background Diabetes is a major public health problem affecting people of all ages globally. Noncompliance compromises the effectiveness of treatment and adversely affects patients' health. The main purpose of this study was to assess and compare the proportion of noncompliance to diet and medication between patients with type 2 diabetes mellitus (T2DM) visiting public and private hospitals in Kathmandu, Nepal.Methods Descriptive cross-sectional study was conducted in T2DM patients visiting public and private hospitals. Eight item Morisky Medication Adherence Questionnaire (MMAQ) for medication adherence and Perceived Dietary Adherence Questionnaire (PDAQ) for dietary adherence were used. Epidata was used for data entry and SPSS for data analysis. Chi-square test was used as a test of significance. Odds ratio (OR) and the corresponding 95% confidence intervals (CI) were calculated.Results The study involved 182 T2DM patients. Participants' age was ≥ 17 years and they were under treatment for ≥ 6 months. Mean age of the participants was 54.67 years with standard deviation (SD) ± 11.69. Prevalence of medication noncompliance was seen in 126 (69.2%) patients, whereas prevalence of dietary noncompliance was seen in 166 (91.2%) patients. Illiterate participants were more likely to be noncompliant than literate to medication (OR 4.32, p = 0.001). Self-employed were more likely to be noncompliant to medication than job holders (OR 2.93, p = 0.008). People visiting public hospital were more likely to be noncompliant to diet than those visiting private hospital (OR 4.89, p = 0.009). Illiterate participants were more likely to be noncompliant to diet than literate (OR 10.94, p = 0.005).Conclusion The T2DM patients visiting public hospitals were more noncompliant to diet. Illiterate patients were more noncompliant to both medication and diet. Self-employed compared with job holders were more noncompliant to medication. Patient education and counseling should be aggressively addressed mainly in public hospitals. There was no significant difference in medication noncompliance between public and private hospitals (p = 0.108).
Keywords: diet; medication; noncompliance; type 2 diabetes mellitus